A Web-Based Information System for Early Childhood Education Licensing Governance using Extreme Programming (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The management of licensing data for Early Childhood Education (ECE) institutions at the Department of Education and Culture of Ogan Ilir Regency previously relied on fragmented spreadsheet-based systems, resulting in data redundancy, limited accessibility, low traceability, and a high risk of information loss. This study aims to develop a centralized web-based licensing information system using the Extreme Programming (XP) methodology to support digital governance and administrative efficiency. The system was developed through four iterative cycles based on user stories and continuous feedback from administrative staff. The application was implemented using the Laravel framework and a MySQL database to ensure system security and data integrity. Functional evaluation was conducted using Black-box Testing and User Acceptance Testing (UAT). The testing results indicate that the system achieved 100 percent functional accuracy and reduced average licensing data processing time from approximately 15 minutes per record to less than 2 minutes. In addition, automated PDF document generation decreased report preparation time from about 20 minutes to less than 10 seconds. User acceptance evaluation showed a satisfaction level of 88%, indicating high usability and operational suitability. These results demonstrate that the application of Extreme Programming, particularly through iterative development and continuous user feedback, contributed significantly to system adaptability and reliability. The developed system enhances administrative efficiency, data consistency, transparency, and regulatory compliance in public sector educational administration.